Transport Coefficients During Drying of solids containing multicomponent mixtures - Gamero, Rafael; Tutor: Martínez, Joaquin (KTH Sweden, 2011)
This study investigated the transport coefficients involved in mass and heat transfer during the drying of a porous solid partially saturated with multicomponent mixtures. It included the coefficients governing liquid transport through the solid, the matrix of multicomponent diffusion coefficients in the liquid phase, and the effective thermal conductivity. / Este estudio investigó los coeficientes de transporte implicados en la transferencia de masa y calor durante el secado de un sólido poroso parcialmente saturado con mezclas multicomponente. Incluía los coeficientes que rigen el transporte de líquidos a través del sólido, la matriz de coeficientes de difusión multicomponente en la fase líquida y la conductividad térmica efectiva.
Thesis (Doctoral in Chemical Engineering) - Sweden, 2011.
Keywords: FENÓMENOS DE TRANSPORTE; TRANSFERENCIA DE MASA; TRANSFERENCIA DE CALOR; CONDUCCIÓN